Prospective study of treatment of extraarticular fractures of distal end radius by cross K wire fixation and cast immobilisation and its comparison with Kapandji’s method of intrafocal pinning anatomically and functionally - Patil, Paresh; Gaonkar, Kiran; Patil, Adish; Gaonkar, Nishant; Gupta, Ketan; Patel, Nirav; Kulkarni, Himanshu (International Journal of Research in Medical Sciences, 2017)
Background: Distal radius fractures account for 17% of all fractures in adults. The fracture of the lower end of radius crushes the mechanical foundation of man’s most elegant tool, the hand. No other fracture has a greater potential to devastate hand function. Extra-articular fractures (type A in the AO classification) require avoidance of malunion with angulation and shortening. Malalignment results in limitation of movement, changes in load distribution, midcarpal instability and an increased risk of osteoarthritis of the radiocarpal joint. Aims and objectives: Treatment of extraarticular fractures of distal end radius by cross K wire fixation and cast immobilisation and its comparison with Kapandji’s method of intrafocal pinning anatomically and functionally. Methods: Total 50 cases were included in the study. First 25 cases were treated by Kapandji’s method and next 25 cases were treated by cross K wire fixation and all cases were given below elbow cast after internal fixation. Patients were followed up at regular intervals and Anatomical and functional outcomes were evaluated in all the patients. Results: In our study anatomical end results were satisfactory in 96% and unsatisfactory in 4% of the subjects treated with cross K wire fixation and 72% and 28% in cases treated by Kapandji’s method whereas Functional end results were excellent in 28% cases, good in 68% cases, fair in 4% case and poor in 0% cases treated with cross k wire fixation and 12%, 60%, 24% and 4% in cases treated by Kapandji’s method. Conclusion: Cross K wire method proved to be better than Kapandji’s method of intrafocal K wire fixation both functionally and anatomically.